2023
DOI: 10.1038/s41598-023-37975-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of whole-grain cereals on fecal microbiota and short-chain fatty acids in dogs: a comparison of rye, oats and wheat

Abstract: Dietary fiber in dog food is reported to promote healthy gut microbiota, but few studies have investigated the effects of whole-grain cereals, which contain a variety of fiber types and other bioactive compounds. The aim of the present study was to compare the effects of diets containing whole-grain rye (RYE), oats (OAT) and wheat (WHE) on fecal microbiota and short-chain fatty acid production. Eighteen dogs were fed three experimental diets, each for four weeks, in a cross-over design. Fecal samples were coll… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…Although a majority of research to date has been performed using probiotics, investigations into prebiotics have been increasing in companion animals. In both cats and dogs, prebiotic complex carbohydrates have demonstrated positive effects on stool quality, digestive health, and the GI microbiome (7,(14)(15)(16)(17)(18). Studies in both humans and animals have found that carbohydrate fermentation by the GI microbiome leads to the increased production of metabolites such as saccharolytic short-chain fatty acids (SCFAs), which have been shown to provide anti-inflammatory and immunomodulatory activity, among other effects (19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…Although a majority of research to date has been performed using probiotics, investigations into prebiotics have been increasing in companion animals. In both cats and dogs, prebiotic complex carbohydrates have demonstrated positive effects on stool quality, digestive health, and the GI microbiome (7,(14)(15)(16)(17)(18). Studies in both humans and animals have found that carbohydrate fermentation by the GI microbiome leads to the increased production of metabolites such as saccharolytic short-chain fatty acids (SCFAs), which have been shown to provide anti-inflammatory and immunomodulatory activity, among other effects (19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%